HYRUDOTHERAPY OF INFLAMMATORY DISEASES OF PERIODONTS - Циганова, Наталія; Велігоря, Ірина; Пушкар, Людмила (Modern engineering and innovative technologies, 2024)
In the conducted study, the clinical justification for the use of hirudotherapy in the treatment of inflammatory periodontal diseases was confirmed. Comprehensive treatment of 152 patients with chronic generalized periodontitis aged 19 to 55 was carried